Challenges of Teaching Physiology Following the Transition From Traditional Curriculum To An Integrated System-Based Curriculum - Hasan, Zuheir; Sequeira, Reginald (Revue canadienne de l'éducation médicale, 2012)
The transformation of a traditional discipline-based medical curriculum into a system-based integrated curriculum often poses dilemmas to faculty involved in teaching basic medical sciences. This paper examines the challenges of teaching physiology to medical students in a system-based curriculum. Some of these challenges include: defining the core curriculum, curriculum links, sequencing curriculum content, interdisciplinary integration, and student assessment. A number of relevant issues including defining the core physiology content, faculty expertise, and coping and adapting to curriculum transitions are discussed from a personal perspective. For successful implementation of a system-based curriculum and to overcome the challenges, educational issues should be debated in regional and international forums.